PERAN LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK SELF-MANAGEMENT DALAM MENGATASI PROKRASTINASI AKADEMIK - Salman Al-Farisi; Lusiana; Isnaul Khoiriyah; Muamanah Nur Ilahiya; Zikrilla Amalia; Fatihatul Luthfiyah; Rusmiyati (Counseling Milenial (CM), 2026)
Academic procrastination is a common behavior among students characterized by delaying the completion of academic tasks, which can lead to decreased academic achievement and increased academic stress. This issue requires appropriate intervention through guidance and counseling services. One of the effective approaches is group guidance using self-management techniques, which aim to help students regulate and control their behavior. This study aims to examine the role of group guidance services using self-management techniques in overcoming academic procrastination among junior high school students. The method used is a literature review by analyzing various relevant scientific sources. The results indicate that group guidance with self-management techniques is effective in reducing academic procrastination by improving time management, discipline, and self-awareness.